A classroom market for extra credit: A semester-long experiment. Issue 4 (1st October 2016) - Staveley-O'Carroll, James
ABSTRACT: This article describes an innovative pedagogical technique, applicable to most economics courses, that offers students a deeper understanding of market equilibrium, inflation, real and nominal interest rates, intertemporal choice, and financial markets. Students earn extra credit, pooled together for the entire class, by correctly answering in-class clicker questions. Correctly answering questions also earns students classroom currency, which they can use to "purchase" extra credit from the pool. The creation and purchase of extra credit establishes an endogenous market system in which the price of extra credit clears the market. The experiment can be augmented with (a) a bank that allows students to borrow classroom currency, (b) bonds to enable direct transfers between students, and (c) stocks that produce randomly generated payouts.